Orthodontic Compensation with extraction and support of hooks in a Class III Malocclusion in an adult patient. Case report - Pajares Ontaneda , Atreyu (2026)
Class III malocclusion is one of the dentoskeletal alterations affecting a significant percentage of the global population. Its etiology is multifactorial, ivolving hereditary, environmental, and skeletal factors. This condition is frequently associated with facial disharmony, which can negatively impact a patient’s self-esteem. The therapeutic approach to Class III malocclusion depends mainly on the severity of the case and the patient’s age. Among the available options, compensatory treatment or orthodontic camouflage is considered a common and effective option in selected cases. The purpose of this case report is to describe the clinical characteristics and therapeutic management of a patient with Class III malocclusion through compensatory treatment involving extractions and loops. Finally, it aims to provide updated information that may serve as a reference for the management of similar cases in clinical practice.